Roma Diktatörlüğü - (:unkn) unknown (My University, 2017)
Roma diktatörlüğü; yasama, yürütme ve yargı güçlerinin bir kişi, organ ya da partide birleşmesine dayalı keyfî bir yönetim sistemi değildi. Aksine diktatörlük; seçilme usulü, görev ve yetkileri, görev süresi, hukukî sorumluluğu başta olmak üzere ana hatları Roma'nın şekli olmayan anayasasınca düzenlenmiş anayasal bir kurumdu. Öte yandan bu kurum, Roma'nın kendine özgü koşullarının bir ürünü değildi. Romalılar, bu eşsiz makamı, kadim ve dinî nitelikli Latin diktatörlüğünden yola çıkarak yaratmışlardır

The Roman dictatorship was not an arbitrary system of government, in which the legislative, executive and judiciary powers are concentrated in one person, organ or party. On the contrary, the dictatorship was a constitutional institution, of which its main aspects, especially the modality of election, duties and powers, term of the office, legal responsibility were regulated by the uncodified Roman constitution. On the other hand, this institution was not issued from purely Roman conditions. The Romans created this unprecedent office after the ancient and religious one of the Latin dictatorship
The Roman Dictatorship
Keywords: Hukuk